2014
DOI: 10.1007/s00455-014-9574-1
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Esophageal Eosinophilia is Not Increased in the Summer Months

Abstract: Smaller studies have suggested seasonal variation of the diagnosis of eosinophilic esophagitis with more patients being diagnosed in the aeroallergen season. We evaluated a large group of adult patients for a seasonal variation of the diagnosis of symptomatic eosinophilic esophageal infiltration. We performed a retrospective review of adult patients from a large Eosinophilic esophagitis database at the Mayo Clinic Rochester. We only included patients from three states in the upper Midwest, who had 15 or more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…One article was a case report, 33 two were case series, 30,34 one was a cross sectional study, 35 nine were case-control, 36-44 and six were cohort studies. 45-50 All articles were written in the last decade, with the earliest published in 2007. One study was conducted in Spain, 35 one in Canada, 40 and another in Australia, 42 with the remaining eleven completed in the US.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One article was a case report, 33 two were case series, 30,34 one was a cross sectional study, 35 nine were case-control, 36-44 and six were cohort studies. 45-50 All articles were written in the last decade, with the earliest published in 2007. One study was conducted in Spain, 35 one in Canada, 40 and another in Australia, 42 with the remaining eleven completed in the US.…”
Section: Resultsmentioning
confidence: 99%
“…41,45,47-50 The first used a retrospective cohort design to compare rates of EoE diagnosis across seasons and adjusted for seasonal esophagogastroduodenoscopy (EGD) case volume. 45 They found that EoE diagnosis was more common in spring and summer, or outdoor months, than winter and fall, or indoor months.…”
Section: Resultsmentioning
confidence: 99%
“…Atopic features and allergy sensitization patterns in EoE patients are not different from those atopic non-EoE individuals living in the same geographical area and exposed to common allergens [33], with no significant differences regarding history of allergic rhinitis, atopic dermatitis, immunoglobulin E-mediated food allergy or sensitization to aeroallergens, and family history of atopy found between children and adults with EoE [34]. A potential role of airborne allergens in triggering the disease has also been suggested after observing seasonal variations in the incidence of EoE [35], but results that have not been universally reproduced [36,37].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…In comparison, a 2013 study of children diagnosed with EoE showed there was no significant association with different seasons and EoE diagnosis (P=0.2035) [19]. A more recent study in 2014 by Elias et al also showed a different trend with peak periods of diagnosis for symptomatic esophageal eosinophilia in December-January (11-13%), and less in May-June (11 -9%) (p=0.014) [20]. Along with aeroallergens, food antigenic triggers exist.…”
Section: Pathogenesismentioning
confidence: 98%